Administrative Decisions in the Era of Artificial Intelligence - Pszczyński, Mateusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The rapid development of cybernetics allows the use of artificial intelligence in many areas of social and economic life. The State can also harness algorithms and machine learning for its actions. Automatic decision making should be one of the stages in the development and improvement of public administration. While it is easy to implement these solutions in the case of related decisions, decisions made under administrative discretion, general clauses or valuation standards pose a challenge. The correct transformation of paper-based public administration into automatic public administration requires a change in decision makers’ thinking, the introduction of new solutions, and building trust in artificial intelligence. Therefore, new solutions have to be built in accordance with the principles of transparency, accountability, equality, goodness and justice. Artificial intelligence making automatic decisions on behalf of the State must be a tool to support the execution of public tasks concerning citizens which is based on trust towards AI and public administration.